OPTIMIZATION OF RESISTANT STARCH FROM BANANA FLOUR CV. MAS KIRANA OFF GRADE TO PRODUCE YOGURT PREBIOTIC - Ermi Sukasih, STP, MSi; nFN Widaningrum; nFN Setyadjit; Winda Haliza (Jurnal Penelitian Pascapanen Pertanian, 2021)
The banana of CV. Mas Kirana off-grade can be processed into banana flour with high resistant starch content which functions as a prebiotic. This study aims to optimize the content of resistant starch (RS) type 3 in the produce of banana flour. Modified banana flour cv. Mas Kirana with highest RS content will then be used to substitute skim milk in making prebiotic banana yogurt and are analyzed for its sensory properties. Data were processed using design expert 11.0 with three factors, namely X1 (Lactic acid bacterial concentration (LAB), X2 (fermentation time), X3 (retrogradation time). The optimization result was 109 CFU/mL of lactic acid bacteria concentration, 24 hours of fermentation time, and 37,60 hours of retrogradation time. The resulting banana flour cv Mas Kirana has 83,95% of resistant starch, 29,24% of yield, 3,60 of logarithmic lactic acid bacteria, and 4,49 of pH value. Its application to the production of banana yoghurt prebiotic replacing 80% skim milk, was acceptable to panelists in terms of color, aroma, viscosity, taste, and overall acceptance.